Politeness in the COVID-19 workplace: The case of University American College Skopje - Marjana Vaneva; Vesna Hristova; Marjan I. Bojadjiev (University American College Skopje, 2021)
This study investigates the level of politeness in the workplace during the COVID-19 pandemic by using the speech acts of request, apology and compliment in English. The organization that is subject to research is University American College Skopje - a private higher-education institution in the Republic of North Macedonia. Organizational communication is essential for the performance of and within one organization and is a crucial part of employees' motivation, employees' retention, positive performance and positive financial outcomes of the organization. On the other hand, being polite in the workplace and following proper workplace etiquette can help managers and workers function as a unit. Hence, as language is the main tool of communication, its effectiveness is analyzed and determined through language analysis done on the use of three speech acts: request, apology and compliment, which are considered to be most commonly used in an organizational setting. The research is conducted with participants who hold administrative and managerial positions at UACS. They are invited to electronically respond to six different situations, which ask them to use the speech acts that are subject to this research: once in a conversation with their fellow colleague on the same level, and then when conversing with their superior - for the administrative positions, and with their subordinate - for the management-positioned respondents. The situations given in the questionnaire are constructed to seem natural for the respondents' particular working environment. For better communication to be achieved, normal circumstances in life and business always recommend using polite language, but the new COVID-19 pandemic, with its urge for physical distancing and isolation, calls for mandatory politeness, to ensure people's mental wellbeing and successful organizational communication. The research shows that, in this pandemic, when communicating through the three speech acts, the UACS employees are highly polite in their organizational communication.
Keywords: 330; politeness; workplace; pandemic; speech acts; organizational communication; UACS case study